THE RELATIONSHIP BETWEEN PARENTS AND SCHOOL ENVIRONMENT WITH EMOTIONAL INTELLIGENCE OF STUDENTS IN MTSN 3 PASAMAN - Siti Hafsoh; Daharnis; Netrawati; Zadrian Ardi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This research is based on low emotional intelligence which is a problem for students in everyday life. Parental support and the school environment can affect students' emotional intelligence. The purpose of this research is to describe; (1) parental support, (2) school environment, (3) emotional intelligence, (4) the relationship between parental support and the emotional intelligence of students, (5) the relationship between the school environment and the emotional intelligence of students, and (6) the relationship between parental support and school environment with the emotional intelligence of students. This study used quantitative research with descriptive methods and the population was students of class VIII and class IX MTsN 3 Pasaman. The sampling technique used is Proportional Stratified Random Sampling with a total sample of 254 respondents. The instrument model is the Likert scale. The reliability instrument for parental support was 0.880, the school environment was 0.861 and emotional intelligence was 0.911. Data were analyzed using multiple regression. The results of the study show that: (1) parental support is in the moderate category. (2) the school environment is in the medium category, (3) emotional intelligence is in the medium category, (4) there is a significant positive relationship between parental support and emotional intelligence, (5) there is a significant positive relationship between the school environment and emotional intelligence ( 6) there is a significant positive relationship between parental support and the school environment with emotional intelligence. The reliability instrument for parental support was 0.880, the school environment was 0.861 and emotional intelligence was 0.911. Data were analyzed using multiple regression. The results of the study show that: (1) parental support is in the moderate category. (2) the school environment is in the medium category, (3) emotional intelligence is in the medium category, (4) there is a significant positive relationship between parental support and emotional intelligence, (5) there is a significant positive relationship between the school environment and emotional intelligence ( 6) there is a significant positive relationship between parental support and the school environment with emotional intelligence.